Wetland elevation change following beneficial use of dredged material nourishment - Harris, Brian D.; Ostojic, Aleksandra; Tedesco, Lenore P.; VanDerSys, Keith; Bailey, Susan; Shawler, Justin L.; Jafari, Navid H.; Chasten, Monica (Frontiers in Ecology and Evolution, 2025)
The beneficial use of dredged material (BUDM) to nourish degrading wetlands is a direct solution to increase surface elevation to help wetlands keep pace with sea level rise (SLR). While there have been numerous demonstrations of BUDM in wetland environments, there is a limited understanding of the resultant spatial and temporal elevation response due to consolidation of the dredged material and underlying wetland foundation soils. To address this, surface elevations were monitored following multiple BUDM nourishments on a back-bay island in New Jersey. Field data was compared to consolidation models to assess the viability of current geotechnical modeling practices. Multispectral surveys were performed to document the revegetation of the nourished island over time. The placement of dredged material smothered the vegetation, but the site experienced significant revegetation (low of 22% cover in August 2021 to 52% in September 2023) after three full growing cycles. Approximately two years post BUDM, the nourished area experienced a 0.19 ± 0.11-m increase in elevation. The comparison of elevation immediately after nourishment and two years post-nourishment found that approximately two-thirds of elevation loss was the result of consolidation of deposited dredged material and the underlying wetland foundation. It was found that a reliance on solely laboratory data can induce a large degree of uncertainty within projected surface elevations. Thus, the implementation of in-situ geotechnical methods is strongly advised when possible. This investigation allowed for a comprehensive examination of geotechnical modeling methods for planning wetland nourishments, including predicting the ability to keep pace with sea level rise. Ultimately, the two BUDM nourishments offset the effects of SLR by approximately 18–28 years.